Rapid calculation of gravity anomalies based on residual node densities and its GPU implementation. (October 2015) - Sheng, Zhang; Xiaohong, Meng; Zhaoxi, Chen; Junjie, Zhou
Abstract: Gravity forward modeling is an important part of three dimensional physical property inversion; however, its time-consuming nature restricts its practical application. Several authors have made efforts to develop this procedure and have achieved some success. This paper proposes a new simple and fast approach for computing gravity anomalies at arbitrary points. In our method, the subsurface is divided into a 3D array of rectangular prismatic blocks, each with a constant density. Then the block density model is transformed into a residual node density model. Finally, gravity anomalies at survey points are calculated using the new residual node density-based forward formula. This method is implemented on a CPU–GPU heterogeneous architecture with the CUDA FORTRAN language and achieves more than four times acceleration compared to the classical method in the same computational environment and two orders of magnitude acceleration compared to one CPU processor on synthetic random density model tests. Highlights: The gravity forward formula was simplified using the residual node density model. The proposed method can reduce the redundant calculations of the classical method. This method was implemented on a CPU–GPU architecture using the CUDA FORTRAN language. The new method runs much faster than the classical method on synthetic model tests.